PENERAPAN ALGORITMA PALGUNADI PADA SPLIT DELIVERY VEHICLE ROUTING PROBLEM UNTUK PENDISTRIBUSIAN MULTI PRODUK - Wulandari, Sri; Kusrini, Kusrini; Arief, M. Rudyanto (Informasi Interaktif, 2019)
Transportation is one area in the supply chain management that determines how and when to send goods to consumers. Determination of distribution routes has an effect on transportation costs. In delivering goods, the company must be able to determine the configuration of the distribution line appropriately so that shipping becomes fast and does not cost much. This study, we will develop a SDVRP solution method for multiple-products distribution. Solving the SDVRP problem for multiple-products distribution will use the Palgunadi Algorithm with the aim of determining the distribution route so that the minimum total distribution costs are obtained. This study uses data about the distribution of fuel in the NTT region with many agents 8 and many types of products 3. There are 3 types of tankers used. The results of the study produced 3 alternative distributions based on the type of tanker used. The use of type 2 (3,500) tankers results in a minimum total distribution cost with the number of routes and tankers used is 2. Keywords: SDVRP, Palgunadi Algorithm, Multiple Products